OPTIMIZATION OF PRODUCT QUALITY CONTROL IN ROBBANI SNACK MSME USING THE SEVEN TOOLS METHOD AND KAIZEN - Suroso, Erdi; Nurainy, Fibra; Hidayati, Sri; Putri, Nadia Eka (Jurusan Teknologi Hasil Pertanian, 2025)
The production process at Robbani Snack MSME was not free from errors, which led to defective products. These defective products were detrimental because they could not be sold, thus reducing profits. Therefore, quality control was necessary so that the company could identify and correct any damage or deviations in its production, especially for cassava chips and purple sweet potato chips. The purpose of this research was to determine the types and causes of defects and to provide improvement recommendations to address product defects at Robbani Snack MSME. The research that was conducted on the production process of cassava chips found three types of defects, namely burnt defects, crushed defects, and dirty defects, with the largest percentage of defects being crushed defects at 74%. The production process of purple sweet potato chips found three types of defects, namely pitted defects, crushed defects, and dirty defects, with the largest percentage being pitted defects at 82%. The causes and solutions for product defect improvements were identified using the Kaizen method, focusing on five main factors: man, machine, material, methods, and measurement. The recommendations that could be implemented included creating SOP, conducting regular training for employees, replacing manual processes with automated machines, implementing clear raw material standardization with the right varieties, selecting reliable suppliers with guaranteed raw material quality, implementing SOP for the production process, and developing an effective measurement system using accurate tools, as well as collecting feedback from consumers regarding product satisfaction. Keywords: Quality, defects, quality control, seven tools, Kaizen.